Pengaruh Mindfulness dan Organizational Citizenship Behavior (OCB) terhadap Kinerja Pegawai dengan Motivasi Intrinsik sebagai Variabel Mediasi - Setiawan, Dody; Nurhidayati, Nurhidayati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research aims to analyze the influence of mindfulness and Organizational Citizenship Behavior (OCB) on employee performance with intrinsic motivation as a mediating variable. The study was conducted on employees of the East Kalimantan Province Bank Indonesia Representative Office using a quantitative approach through a questionnaire filled in by 148 respondents. Data analysis uses the Structural Equation Modeling (SEM) method with SmartPLS. The research results show that mindfulness has a significant positive influence on employee performance, but not significantly on intrinsic motivation. This is influenced by the characteristics of the millennial generation who tend to like instant results and work-life balance, so that mindfulness is less effective in increasing intrinsic motivation. To overcome this, integration of mindfulness with other variables that give work meaning is necessary. OCB has been proven to have a significant positive effect on intrinsic motivation and employee performance. Intrinsic motivation also has a significant effect on employee performance. However, mindfulness did not influence performance through intrinsic motivation. Intrinsic motivation is more influenced by other factors such as job satisfaction, challenges and personal achievements. OCB has a significant influence on performance with intrinsic motivation as mediation. This study expands the literature on mindfulness, OCB, and intrinsic motivation. Practically, it is important to implement structured mindfulness programs and promote OCB. Research limitations include the limited institutional scope and cross-sectional design, so further research is needed to generalize the results.